2021
DOI: 10.3389/fanim.2021.699262
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultraviolet Light for Poultry Production: A Review of Impacts on Behavior, Physiology, and Production

Abstract: The application of ultraviolet (UV) light in poultry production is garnering increased interest with the drive toward improved poultry welfare and optimized production. Poultry can see in the UV spectrum (UVA wavelengths: 320–400 nm) thus inclusion of these shorter wavelengths may be viewed as more natural but are typically excluded in conventional artificial lights. Furthermore, UVB wavelengths (280–315) have physiological impact through stimulation of vitamin D pathways that can then improve skeletal health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 113 publications
(179 reference statements)
0
13
1
Order By: Relevance
“…The sunlight spectrum contains all forms of ultraviolet (UV) radiation: UVA (315-400 nm), UVB (280-315 nm), and UVC (100-280 nm), of which only UVA and UVB reach the earth's surface. Hens can visually perceive UVA and UVB has a physiological effect on the synthesis of vitamin D3 in featherless skin [31]. However, high intensities and/or overexposure of UV radiation may have damaging effects [32,33], and, thus, hens might avoid direct sunlight at its most intense.…”
Section: Introductionmentioning
confidence: 99%
“…The sunlight spectrum contains all forms of ultraviolet (UV) radiation: UVA (315-400 nm), UVB (280-315 nm), and UVC (100-280 nm), of which only UVA and UVB reach the earth's surface. Hens can visually perceive UVA and UVB has a physiological effect on the synthesis of vitamin D3 in featherless skin [31]. However, high intensities and/or overexposure of UV radiation may have damaging effects [32,33], and, thus, hens might avoid direct sunlight at its most intense.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, during the hen counts in this study, more birds were observed outside on cloudy days, similar to an observation reported by Whay et al [ 44 ] during visits to 25 commercial free-range farms in the UK where they noticed that maximum use of the range happened on calm, cloudy days. UV supplementation in indoor settings can improve hens’ behavioural repertoire and skeletal heath [ 7 ] and hens will show preferences for low levels of UV AB light compared to UV deficient environments [ 33 , 52 ]. This may support the birds’ greater use of the ‘sun’ range area in the morning and late afternoon, but when the radiation is at its peak irradiance, hens avoid this, similar to hens exhibiting preferences for shelters that block more UV radiation [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Free-range hens get exposure to sunlight for at least part of the day with access to move freely in an outdoor area rather than continuous indoor housing. The outdoor exposure provides hens the opportunity to access natural vitamins from herbage, and vitamin D 3 from ultraviolet (UV) radiation in sunlight [ 5 7 ] in addition to what is provided in their formulated feed. Ranging outside may also reduce feather pecking behaviour to improve plumage coverage and encourage greater expression of natural behaviours such as foraging, walking, and dust bathing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A periodic cleaning schedule is suggested when applying the system in poultry houses. Next, even though UVA (wavelength of 315–400 nm) was well studied and proven that it had positive effects on poultry [ 27 ], UVC (wavelength of 200–300 nm) was not well studied yet. Therefore, the application of UVC, in this case, 254 nm, into the poultry environment also needs to consider its impact on the poultry.…”
Section: Discussionmentioning
confidence: 99%